Levetiracetam Versus Phenytoin or Fosphenytoin for Second-Line Treatment of Pediatric Status Epilepticus: A Meta-Analysis. Issue 9 (12th March 2021) - Klowak, Jennifer Ann; Hewitt, Mark; Catenacci, Vanessa; Duffett, Mark; Rochwerg, Bram; Jones, Kevin; Choong, Karen
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVE: To synthesize the available evidence examining the efficacy and safety of levetiracetam compared with phenytoin or fosphenytoin in benzodiazepine-refractory pediatric status epilepticus. Data Sources: We searched (from inception until April 27, 2020) Ovid MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. Study Selection: Two reviewers, independently and in duplicate, screened citations and manuscripts for eligible randomized controlled trials. Data Extraction and Synthesis: Independently and in duplicate, we performed data abstraction, risk of bias assessment, and certainty assessment using Grading of Recommendations, Assessment, Development, and Evaluation. We performed meta-analyses using random-effect models or, if insufficient data, presented findings narratively. Results: We identified seven randomized controlled trials ( n = 1, 575). Pooled analysis demonstrated low certainty evidence for no difference of levetiracetam on time to seizure cessation (mean difference, –3.11 min; 95% CI, –6.67 to 0.45), early seizure cessation (relative risk, 1.09, 95% CI, 0.95–1.26), or late seizure cessation (relative risk, 1.05; 95% CI, 0.93–1.18). Adverse event outcomes were limited by low event numbers. We found low certainty evidence for less respiratory depression with levetiracetam (relative risk, 0.28; 95% CI, 0.12–0.69). Conclusions: The efficacy of levetiracetam is comparable with phenytoin or fosphenytoin in children with benzodiazepine-refractory status epilepticus (low certainty evidence). Levetiracetam may cause less respiratory depression. Clinicians and guideline developers should weigh safety profiles when choosing between these agents.